Penggunaan Media Ajar Video dalam Pembelajaran Nilai-Nilai Teks Hikayat pada Siswa SMK Negeri 7 Semarang - Nadia Intansari; Asrofah Asrofah; Sri Kismiyati (FKIP Universitas Khairun, 2024)
This article presents the results of a research that describes the use of video media in learning the values of hikayat texts to class X students at SMK Negeri 7 Semarang. The purpose of this study is to describe the use of video media, find out the learning steps, and assess the learning outcomes of students in learning the values of hikayat texts. This research uses a mixed approach that involves quantitative and qualitative data collection. Data collection was conducted using test and non-test techniques (observation and documentation). Data analysis techniques used triangulation techniques by testing the validity of the data collected by researchers to obtain data and enrich the insights of research informants. Overall, students succeeded in achieving the Criteria for Achieving Learning Objectives (KKTP) with a range of scores between 78-100% and the average percentage value was 86%. The results showed that the use of video media in learning to analyze the values of hikayat texts at SMK Negeri 7 Semarang had a positive impact and was successfully applied to the learning of saga texts to class X students at SMK N 7 Semarang.